ANALISIS PENGETAHUAN TERHADAP KEJADIAN ANEMIA IBU HAMIL TRIMESTER III - odilia esem; Frida Sisternike Pay (STIKes CHMK, 2023)
Anemia is a condition in which a person does not have enough red blood cells to deliver oxygen to various tissues in the body. Experiencing anemia can make a person feel tired and weak. Anemia in pregnant women can increase the risk of premature birth, maternal and child mortality, and infectious diseases. This study aims to determine the relationship between maternal knowledge and the incidence of anemia in third trimester pregnant women. This study uses a Cross Sectional Analytic design. The number of samples in this study were 50 respondents. The sampling technique uses total sampling. Data collection was carried out from March to April 2023. Data analysis consisted of univariate and bivariate analysis. Bivariate analysis was used to determine the relationship between the two variables, namely knowledge of the mother with anemia using the Chi-square test with a significance degree of p<0.005. The results of the statistical analysis test with Chi-Square obtained p <0.005 (p = 0.000) so that it can be interpreted that there is a very significant relationship between knowledge of pregnant women about anemia and the incidence of anemia. The conclusion in this study is a very significant relationship between the knowledge of pregnant women about anemia and the incidence of anemia. Keywords: Knowledge, Anemia, Pregnancy.